Trzy sztuki Kazimierza Gołby na katowickiej scenie (PDF 1,87 MB) (Książnica Śląska, 2025)
The article discusses the realisations of three plays by Kazimierz Gołba: Rekruci, My – Pierwsza Kadrowa and Lompa. The first two playswere recorded at the Polish Theater in Katowice in 1935, the latterwas an important post-war premiere of the Silesian Theater in June1945. As noted by Krystian Węgrzynek, Gołbas dramaturgic textsmirror his journalistic activity and constitute the author’s voice in theongoing debates. In these works the influences of modernist dramaare noticeable: historical and naturalistic drama, but also the fascination with monumental drama under the sign of Leon Schiller orWilam Horzyca